Generation Z in the Digital Era Navigating Information Overload and Its Influence on Decision Postponement - Loing, Chenly; Roosdhani, Mohamad Rifqy; PR, M Rivi Putra (JOURNAL OF ADVANCED STUDIES IN MANAGEMENT, 2025)
This study investigates the relationships among information overload, consumer confusion, and decision postponement in Generation Z consumers in Jepara. In the digital era, Generation Z is continuously exposed to vast amounts of information, which can lead to cognitive strain and impact their decision-making processes. Employing a quantitative approach, data were collected from 310 respondents using an online survey and analyzed through Partial Least Squares-Structural Equation Modelling (PLS-SEM). The findings reveal that information overload has a significant positive effect on consumer confusion, indicating that an excess of information increases the likelihood of confusion during the decision-making process. Furthermore, consumer confusion is found to significantly drive decision postponement, suggesting that when consumers experience confusion, they are more likely to delay making purchasing decisions. However, the study finds no significant direct effect of information overload on decision postponement; instead, the effect is mediated by consumer confusion. These results highlight the pivotal mediating role of consumer confusion in the relationship between information overload and decision postponement. The study contributes to the literature by clarifying the psychological mechanisms underlying digital consumer behavior among Generation Z and provides practical implications for marketers to design more effective communication strategies in hyper-connected environments.. Keywords— consumer confusion; decision postponement; information overload